Development of E-Comic to Increase the Spirit of Mutual Cooperation and Learning Achievement of Elementary School Students - Zeva Adi Fianto; Fitri Indriani; Anwar Senen; Cici Oktaviani; Dewi Nasien (Elementary Teacher Education Program, Majalengka University, 2024)
Technology has a big positive impact on integration in the world of education. The aim of this research is to produce an e-comic about my environment to increase the spirit of mutual cooperation and appropriate, practical and effective learning achievements. This development research uses the ADDIE research model. The research subjects were 102 students and 4 teachers at elementary school cluster II, Kasihan subdistrict, Bantul district, Yogyakarta. Data collection techniques used interviews, needs analysis questionnaires, validation questionnaires, response questionnaires, self-assessment questionnaires, and pretest posttest. Data analysis used the independent sample t-test, paired sample t-test, and MANOVA test. The results of the independent sample t-test show a significant value of 0.019<0.05. The results of the paired sample t-test show a significant value of 0.002 <0.05. The MANOVA test results show a significant value of 0.006<0.05. Overall, there is a significant difference in the spirit of mutual cooperation and learning achievement between students who use e-comics and those who do not use the results of research on the development of e-comic material my environment. The spirit of mutual cooperation and learning achievement of students who use e-comics increases compared to those who do not use e-comics. It was concluded that e-comics were declared feasible, practical and effective for use as learning media.